2017
DOI: 10.17235/reed.2017.4994/2017
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of infection and diversity of Helicobacter pylori strains in an adult population in Mexico treated with empirical standard triple therapy.

Abstract: The recurrence of infection in this study was higher than that recorded in developed countries with a low prevalence of H. pylori and lower than that recorded in developing countries with a higher prevalence of H. pylori. The cagA or vacA s2/m2 strains were isolated after re-infection and recrudescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Literature suggests that recurrence rates in developing countries are much higher than those in developed countries (11,12). For example, the annual recurrence rate in Latin America is 11.2% (13), while it is 9.3% in Mexico (14). A study in South Korea reported a recurrence rate of 10.9% following eradication (15), and in Vietnam, the reinfection rate was 23.5% after 11 months of follow-up (16).…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that recurrence rates in developing countries are much higher than those in developed countries (11,12). For example, the annual recurrence rate in Latin America is 11.2% (13), while it is 9.3% in Mexico (14). A study in South Korea reported a recurrence rate of 10.9% following eradication (15), and in Vietnam, the reinfection rate was 23.5% after 11 months of follow-up (16).…”
Section: Discussionmentioning
confidence: 99%